1992
DOI: 10.1182/blood.v79.10.2540.bloodjournal79102540
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter randomized study comparing cyclosporine-A alone and antithymocyte globulin with prednisone for treatment of severe aplastic anemia

Abstract: We report the results of a randomized multicenter study comparing the efficacy of antithymocyte globulin (ATG) with that of cyclosporin A (CsA) as first-line therapy for severe aplastic anemia (SAA). Patients were randomized to receive ATG and prednisone (PDN) or CsA; hematologic response and toxicity were compared. At 3-month evaluation, patients who had no or minimal response received the alternative therapy to assess the value of a sequential immunosuppressive therapy for treatment of severe aplastic anemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…Unexpectedly, we observed a rather high remission rate and rather short interval to response in patients with SAA (47% and 8 weeks). This differs strikingly from the results of a study by Gluckman et al (1992) comparable with our series in the number of patients included, who reported responses at 3 months in only 11´6% of patients treated with CsA. Most probably this difference is best explained by the fact that, unlike the above-mentioned study where the median interval from diagnosis to treatment was <1 month, in our cohort it was 5 months.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, we observed a rather high remission rate and rather short interval to response in patients with SAA (47% and 8 weeks). This differs strikingly from the results of a study by Gluckman et al (1992) comparable with our series in the number of patients included, who reported responses at 3 months in only 11´6% of patients treated with CsA. Most probably this difference is best explained by the fact that, unlike the above-mentioned study where the median interval from diagnosis to treatment was <1 month, in our cohort it was 5 months.…”
Section: Discussioncontrasting
confidence: 99%
“…Although CsA is being used widely as a component in combined immunosupressive therapy, very little is known about the value of long-term therapy with CsA alone. In the only published randomized study aimed at comparing ATG with CsA, most patients not responding to CsA within 3 months were crossed over to ATG therapy and vice versa (Gluckman et al, 1992). Interestingly, in this study 50% of the nonresponders in whom CsA therapy was mistakenly continued remitted later.…”
mentioning
confidence: 80%
“…This drug reportedly induces remission in 30-40% of patients with AA. A recent controlled study by a French group has revealed that CyA is at least as effective as antithymocyte globulin (ATG), the most suitable therapy for AA (Gluckman et al, 1992). The advantages of CyA include the fact that it can be given on an outpatient basis and it causes fewer sideeffects.…”
Section: Discussionmentioning
confidence: 99%
“…4 Cyclosporine is an effective drug and is widely administered to prevent graft rejection of solid organ and bone marrow transplants; it has also been successful in the treatment of bone marrow failure disorders. 5,6 Largely based on data from animal models, cyclosporine is thought to precipitate crises in patients with acute porphyria and, therefore, has been considered contraindicated for patients with the disease. 7 Despite this, two published case reports have described the use of cyclosporine in patients with acute intermittent porphyria who underwent kidney transplantation.…”
Section: (Pharmacotherapy 2006;26(11):1662-1666)mentioning
confidence: 99%
“…Based on published case reports indicating that cyclosporine can be administered safely after kidney transplantation in patients with acute intermittent porphyria, 8,9 treatment was started with cyclosporine, which has been shown to be an effective therapy for Tcell-mediated bone marrow failure. 5,6 A baseline 24-hour urine porphobilinogen level was established, and the patient received a test dose of oral cyclosporine 50 mg. A repeat porphobilinogen level was obtained 24 hours later. The patient tolerated the test dose with no symptoms or increases in the repeat porphobilinogen level.…”
Section: Case Reportmentioning
confidence: 99%